Ticagrelor inhibits platelet aggregation and reduces inflammatory burden more than clopidogrel in patients with stages 4 or 5 chronic kidney disease - Jain, Nishank; Corken, Adam; Arthur, John M.; Ware, Jerry; Arulprakash, Narenraj; Dai, Junqiang; Phadnis, Milind A.; Davis, Otis; Rahmatallah, Yasir; Mehta, J.L.; Hedayati, S. Susan; Smyth, Susan (Vascular pharmacology, 2023)
No study has compared pharmacologic properties of ticagrelor and clopidogrel in non-dialysis patients with stage 4–5 chronic kidney disease (CKD). We conducted a double-blind RCT to compare effects of ticagrelor and clopidogrel in 48 CKD, with the primary outcome of ADP-induced platelet aggregation (WBPA) after 2 weeks of DAPT. In a parallel arm, we compared effects of 2 weeks of ticagrelor plus aspirin on mean changes in WBPA and markers of thromboinflammation among non-CKD controls (n = 26) with that of CKD in the ticagrelor-arm. Average age of CKD was 53.7 years, with 62% women, 54% African American, and 42% with stage 5 CKD. Ticagrelor generated statistically lower WBPA values post treatment [median 0 Ω (IQR 0, 2)] vs. clopidogrel [median 0 Ω (IQR 0, 5)] (P = 0.002); percent inhibition of WBPA was greater (87 ± 22% vs. 63 ± 50%; P = 0.04; and plasma IL-6 levels were much lower (8.42 ± 1.73 pg/ml vs. 18.48 ± 26.56 pg/ml; P = 0.04). No differences in mean changes in WBPA between CKD-ticagrelor and control groups were observed. Ticagrelor- DAPT reduced levels of IL-1α and IL-1β in CKD-ticagrelor and control groups, attenuated lowering of TNFα and TRAIL levels in CKD-ticagrelor (vs controls), and had global changes in correlation between various cytokines in a subgroup of CKD-ticagrelor subjects not on statins (n = 10). Peak/trough levels of ticagrelor/metabolite were not different between CKD-ticagrelor and control groups. We report significant differences in platelet aggregation and anti-inflammatory properties between ticagrelor- and clopidogrel-based DAPT in non-dialysis people with stage 4–5 CKD. These notable inflammatory responses suggest ticagrelor-based DAPT might lower inflammatory burden of asymptomatic patients with stage 4 or 5 CKD. (clinicaltrials.gov # NCT03649711). [Display omitted]